(untitled) (Journal of Bio-Science, 2023)
This study evaluated the growth and reproductive activity of Thai sharpunti Barbonymus gonionotus in the L-shaped freshwater pond at Rajshahi University campus of northwest Bangladesh during January and August, 2017. Length and weight increment was recorded for the growth study and gonado-somatic index (GSI) with fecundity was estimated for the assessment of reproductive activity. During the study a significant length and weight increment was observed (p<0.05). Monthly mean total length (TL) ranged 11.76 to 22.47 cm, fork length (FL) was 10.02 to 19.12 cm, standard length (SL) was 8.87 to 16.83 cm and body weight (BW) was 19.89 to 167.81g. Both the length-length relationship (LLR) and length-weight relationship (LWR) showed a positive allometric growth pattern of the fish and the relationships were TL = 1.1759 FL - 0.035, TL = 1.338 SL - 0.0002, FL = 1.0988 SL + 0.6557 and BW = 0.0051TL 3.347. Gonadal observation showed that the fish initiated sexuality in the month of April and was fully matured in the month of May. During the study male female ratio was significantly different from the 1:1 ratio (χ2 = 3.84, p<0.05) and the overall male to female sex ratio was 1:1.42. The gonado-somatic index (GSI) was ranged from 3.72 to 32.39 and showed significant monthly fluctuations (p<0.05). A sharp decline of GSI during May and June indicates the peak spawning of B. gonionotus in the study site. During the study the fecundity of the fish was ranged from 46145 to 353969 and the highest fecundity was recorded in the months of May. The findings of the present study would be helpful for the sustainable management of B. gonionotus in the freshwater ecosystem of Bangladesh and elsewhere. J Bio-Sci. 30(1): 101-114, 2022 (June)